The prevalence and age of onset of psychiatric disorders in Australian men. (July 2016) - Williams, Lana J; Jacka, Felice N; Pasco, Julie A; Coulson, Carolyn E; Quirk, Shae E; Stuart, Amanda L; Berk, Michael
Objective: Given the burden of common psychiatric disorders and their consequent service and planning requirements, it is important to have a thorough knowledge of their distribution and characteristics in the population. Thus, we aimed to report the prevalence and age of onset of mood, anxiety and substance-use disorders in an age-stratified representative sample of Australian men. Method: Psychiatric disorders (mood, anxiety and substance-use disorders) were diagnosed utilising a structured clinical interview (Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders–Fourth Edition, Non-Patient Edition) for 961 men aged 24–98 years enrolled in the Geelong Osteoporosis Study. The lifetime and current prevalence of these disorders was determined from the study population and standardised to 2006 census data for Australia. Results: Approximately one in three men (28.8%, 95% confidence interval [CI] = [26.8%, 30.8%]) reported a lifetime history of any psychiatric disorder, with mood disorders (18.2%, 95% CI = [15.2%, 21.2%]) being more prevalent than anxiety (7.2%, 95% CI = [5.0%, 9.4%]) and substance-use disorders (12.9%, 95% CI = [9.7%, 16.0%]). Approximately 8.7% (95% CI = [7.5%, 10.0%]) were identified as having a current disorder, with 3.8% (95% interquartile range [IQR] = [2.2%, 5.4%]), 2.4% (95% CI = [1.1%, 3.8%]) and 3.4% (95% CI = [1.8%, 4.9%]) meeting criteria for current mood, anxiety and substance-use disorders, respectively. The median age of onset for mood disorders was 37.5 years (IQR = 27.0–48.0 years), 25.0 years (IQR = 20.0–40.3 years) for anxiety and 22.0 years (IQR = 18.0–34.3 years) for substance-use disorders. Conclusion: This study reports the lifetime and current prevalence of psychiatric disorders in the Australian male population. These findings emphasise the extent of the burden of these disorders in the community.